Quantification of pro-inflammatory cytokines and osteoclastogenesis markers in successful and failed orthodontic mini-implants (Journal of Applied Oral Science, 2022)
Objectives: Miniscrew has been frequently used, considering that anchorage control is a critical point in orthodontic treatment, and its failure, the main adverse problem. Using two groups of stable (successful) and unstable (failed) mini-implants, this in vivo study aimed to quantify proinflammatory cytokines IL-1 α, IL-6, IL-17, and TNF-α and osteoclastogenesis marker RANK, RANKL, and OPG in gingival tissue, using the real-time polymerase chain reaction technique. Methodology: Thirteen patients of both sexes (11-49 years old) under orthodontic treatment were selected, obtaining 11 successful and 7 failed mini-implants. The mini-implants were placed and removed by the same surgeon, in both jaws. The mean time of permanence in the mouth was 29.4 months for successful and 7.6 months for failed mini-implants. At removal time, peri-mini-implant gingival tissue samples were collected and processed for quantification of the proinflammatory cytokines and osteoclastogenesis markers. Nonparametric Wilcoxon rank-sum test considering the clusters and Kruskal-Wallis test were used for statistical analysis (α=0.05). Results: No significant difference (p>0.05) was observed between the groups for either quantification of cytokines or osteoclastogenesis markers, except for IL-6 (p<0.05). Conclusions: It may be concluded that the expression of IL-1α, IL-17, TNF-α, RANK, RANKL, and OPG in peri-implant gingival tissue were not determinant for mini-implant stability loss, but the higher IL-6 expression could be associated with mini-implant failure.